Low numbers of post-term pregnancy inductions result in high numbers of emergency caesarean sections. A comparison of morbidity and mortality between term and post-term deliveries in the Murmansk County Birth Registry 2006-2011 - Nedberg, Ingvild Hersoug (UiT Norges arktiske universitet, 2016)
Objective: This thesis compares women who went into spontaneous labour at term with women who gave birth post-term with regards to five outcome variables: perinatal mortality, threatening intrauterine asphyxia, Apgar score below 7 (after 5 minutes), meconium staining and emergency caesarean section. Material and methods: The thesis used data from the Murmansk County Birth Registry from 2006 to 2011. The final study group consisted of 41 417 women of which 1 895 gave birth post-term and 39 522 at term. Logistic regression analysis was used to compare the groups. Results: The main results are that the women in the post-term group had statistically significant higher odds of emergency caesarean section (OR 1.33, 95% CI 1.16 – 1.52), threatening intrauterine asphyxia (OR 1.37, 95% CI 1.17 – 1.61) and meconium staining (OR 1.49, 95% CI 1.32 – 1.69) compared with women in the term group. The odds for perinatal mortality (OR 1.04, 95% CI 0.48 – 2.23) and Apgar score below 7 (after 5 minutes) (OR 1.17, 95% CI 0.75 – 1.83) were not statistically significant. Conclusion: The most important finding of the study is that the odds of emergency caesarean section were 33% higher for the women in the post-term group compared with the term group. The possible implications of this finding are unnecessary high costs for the health care system, and increased morbidity for the women and children in the North-West Russia. The odds of experiencing threatening intrauterine asphyxia and meconium staining were also higher for women in the post-term group compared with the term group, which can lead to interventions such as emergency caesarean section, where threatening intrauterine asphyxia would act as a mediator, and an affected baby. The birth institutions in Murmansk County should consider inducing more women for post-term pregnancy when reaching 42+0 weeks.